Response—Factions for the Rest of Us - John D. Inazu (Washington University Law Review, 2012)
This response paper highlights the author's three objectives in writing Liberty‟s Refuge: one diagnostic, one historical, and one normative. The diagnosis highlights difficulties with the current doctrine of intimate and expressive association. The history excavates the prominent role that the right of assembly occupies in our constitutional and popular past. The normative theory contends that we ought to protect dissenting private groups even at the cost of stability and uniformity. The introductory remarks by Professor Magarian and the three essays from Professors Bhagwat, Vischer, and Appleton address these objectives through generous engagement and thoughtful critique. In the limited space of this response, this comment focuses on six themes prompted by the commentators: expression, violence, relationality, power, funding, and commerciality.
Keywords: & quot; Liberty& #x27; s Refuge: The Forgotten Freedom of Assembly& quot; John Inazu; Freedom of assembly; Right to exclude; Group rights